The Conceptual Design e-Wallet for Rupiah Digital - Zulmy, Mohamad Faisal; Kurniawati, Monica Vivi; Yazid, Setiadi (Jurnal Ilmu Komputer dan Informasi, 2025)
This research study the advancement of Central Bank Digital Currencies (CBDCs) spurred by fi-nancial technology progress. It focuses on Rupiah Digital, Indonesia's CBDC initiative led by the Bank of Indonesia (BI). The study explores the technical aspects of Wholesale and Retail Digital Rupiah, proposes an e-wallet system for seamless digital transactions in related to blockchain technology, specifically Permissioned Distributed Ledger Technology (DLT). The objective of this research to provide recommendations to BI regarding appropriate e-wallet conceptual design based on study literature review (LR) methods and qualitative research method by conducting interviews throughs forum group discussion (FGD) and e-mail with leading economic (banks), legal (BI and Government), and technical experts (banks, academic expert on this field, BI and Government) to get reviews and input regarding the e-wallet conceptual design that was proposed. As result, we recommended the architecture for Rupiah Digital using Hyperledger Fabric blockchain with two-tiered distribution and user layer backed by digital token using ID on mobile apps to enhance the security of the system. The FGD with experts and executor result in approval on those conceptual design to be part of the option on development of CBDC in Indonesia.